Stock Assessment of Tylosurus sp. Using Length Data for Sustainable Management - Nurlette, Hartono; Alimudi, Saiful; Mahelatu, Armina; Lipugena, Harisa (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
The declining condition of global fish stocks threatens the sustainability of the resource. Periodic assessments must address this wisely, especially on economically important fish. This study aims to assess the stock of Tylosurus sp. for sustainable management. Length measurements were taken from fishermen's catches over four months. The analysis was carried out using the TropFishR package in the R program. The results showed that the stock of Tylosurus sp. was underfished with the current exploitation rate at (E=0.48). The total mortality is (Z=1.47 year-1), natural mortality is (M=0.77 year-1), and fishing mortality is (F=0.70 year-1). From the modelling results, the maximum catch can be done up to 1.5 year-1, with the length at the first capture of Tylosurus sp. being 63.3 cm. So, with the current stock condition, fishing can still be increased as long as fishermen need to pay attention to the length of fish caught, which should not be less than the value of the first capture.